Entry to the labour market after completion of qualification : how does integration into working life succeed? - Dorau, Ralf [Verfasser]; Herter-Eschweiler, Robert [Verfasser] (My University, 2019)
"Germany has a low level of youth unemployment in international comparative terms. Practice-related (dual) training is often cited as a reason for this. But how do young people succeed in making the transition to the labour market and thus achieve integration into working life? This article uses data from the microcensus to analyse occupational integration approximately two years after successful completion of a vocational or higher education qualification." (authors' abstract; BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; Ausbildungsabsolvent; Berufseinmündung; Zweite Schwelle; Berufsabschluss; Studienabschluss; Berufliche Integration